Attempted Suicide Among Adolescents in Military Families: The Mediating Role of Adverse Childhood Experiences. Issue 23 (December 2021) - Clements-Nolle, Kristen; Lensch, Taylor; Yang, Yueran; Martin, Heather; Peek, Julia; Yang, Wei
Research has shown that adolescents in military families have higher rates of suicidal behaviors compared to their nonmilitary peers. This is typically attributed to military-specific stressors, but exposure to adverse childhood experiences (ACEs) may also play a role. Our primary research objective was to determine whether cumulative exposure to ACEs mediates the relationship between military family involvement and attempted suicide. A two-stage cluster random sampling design was used to randomly sample 5, 336 students from 98 high schools. Students were asked whether a parent or other adult in their home was serving on active duty in the military and attempted suicide in the past 12 months was assessed. Six measures of childhood abuse and household dysfunction were summed, and the ACE score was categorized as 0, 1, 2, and 3–6 ACEs. Weighted logistic regression and multinomial regression were used to assess differences in ACEs and attempted suicide, controlling for sex, age, race/ethnicity, rurality, and qualification for free/reduced lunch. To investigate potential mediation effects of ACEs on the relationship between military family and attempted suicide, we conducted path analyses controlling for demographics. Compared to their peers, students in military families had higher exposure to ACEs (1 ACE: adjusted odds ratio [AOR] = 1.49, 95% confidence interval [CI] = [0.88, 2.53], 2 ACEs: AOR = 2.07, 95% CI = [1.23, 3.48], and 3–6 ACEs: AOR = 2.57, 95% CI = [1.54, 4.27]) and twice the odds of attempting suicide in the past 12 months (AOR = 2.16, 95% CI = [1.30, 3.61]). Mediation analyses showed that cumulative exposure to ACEs completely mediated the relationship between military family involvement and attempted suicide. The study results highlight the need for trauma-informed approaches to mental health promotion with military families.